PEMETAAN LITERASI INFORMASI PUSTAKAWAN DI PERPUSTAKAAN NASIONAL REPUBLIK INDONESIA - I Nyoman Nova Wasana; I Putu Suhartika; Richard Togaranta Ginting (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2024)
This research is a quantitative research that aims to determine and identify the mapping of librarian information literacy at the National Library of the Republic of Indonesia. This research was conducted at the National Library of the Republic of Indonesia. The research period was 1 month which was carried out from March 4 to April 4, 2024. The population was 68 librarians while the sample size was 67 librarians. In the sample, this study adopted the total sampling method by dividing the population into subpopulations and taking samples as a whole from each subpopulation. The application of the Big Six method in librarian information literacy at the National Library of the Republic of Indonesia involves six stages. At the task definition stage, librarians are able to identify user information needs and help formulate research questions. At the information search strategy stage, librarians select and plan relevant and reliable information search strategies. At the location and access stage, librarians know the location of information sources and help users access them, both physically and digitally. At the information use stage, librarians help users understand and use the information accessed, and record relevant information. At the synthesis stage, librarians combine information from various sources into a coherent and logical whole. Finally, at the evaluation stage, the librarian assesses the quality and relevance of the information and reflects on the information seeking process for future improvements.